Education, Society and Coming of Age in Ken Loach's "Kes" - Čapková, Eliška (Univerzita Pardubice, 2021)
This bachelor thesis focuses on Ken Loach's view on the state of education and society in 1960s England and its effect on coming of age depicted in his film Kes. The theoretical part defines social realism in British cinema and provides more information about Ken Loach. Furthermore, it deals with the social and historical background of the film and also with the school system in 1960s England. The practical part has its base in the theoretical part. It analyses the message of Kes by focusing on Loach's depiction of the challenges of coming of age and the impacts of social class. The last chapter compares Loach's Kes with Barry Hines' novel A Kestrel for a Knave, which served as a basis for this film.
Škola, společnost a dospívání ve filmu
Keywords: Loach, Ken; britská kinematografie; školství; společnost; severní Anglie; 60. léta; dělnická třída; Loach, Ken; British cinema; education; society; Northern England; 1960s; working-class